Literasi Buku Bacaan Guna Meningkatkan Kompetensi Peserta Didik Sekolah Dasar Negeri 6 Indralaya Sumatera Selatan - Miftakhul Ulum; Adita Nafisa (Jurnal Pengabdian Masyarakat: Tipis Wiring, 2024)
This dedication aims to enhance competencies through literacy at State Elementary School 6 Indralaya, South Sumatra. It employs a qualitative descriptive method with a case study approach, utilizing lecture, summarization, presentation, and discussion techniques for data collection. The focus is on improving rapid reading, careful reading, and comprehension skills, including expanding vocabulary. Current elementary school students struggle with reading and understanding texts, yet they are required to comprehend literacy and numeracy in the Minimum Competency Assessment (AKM). Literacy processes are considered efforts to prepare students for the AKM. Through a complex approach, this dedication provides profound insights into how literacy in reading books can have a positive impact and support Indonesia's literacy achievements globally. This activity can serve as a starting point for developing a more effective literacy program at the elementary school level.